2019
DOI: 10.1111/jvh.13097
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hepatitis B core‐related antigen levels and sustained HBeAg seroconversion in patients treated with nucleo(s)tide analogues

Abstract: Summary Hepatitis B e antigen (HBeAg) seroconversion experienced during nucleo(s)tide analogue (NUC) therapy is often not sustained. We aimed to study whether hepatitis B core‐related antigen (HBcrAg) levels predict sustained HBeAg seroconversion in patients treated with NUCs. We studied HBeAg‐positive patients treated with NUCs for at least 6 months. We quantified HBcrAg at baseline and at the time of HBeAg seroconversion and studied the relationship with HBeAg seroconversion and subsequent relapse. HBcrAg wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Several studies have shown that baseline levels and changes in HBcrAg while on antiviral therapy may predict HBeAg loss or seroconversion after patients receive nucleos(t)ide analog or peginterferon therapy. [ 18 , 19 , 36 ] Wang et al [ 18 ] discovered that a combination of HBcrAg and HBsAg levels at month 6 (with AUROC 0.769) or month 12 (with AUROC 0.807) had the greatest predictive value for HBeAg seroconversion, in which 36.4% (43/118) of patients achieved HBeAg seroconversion after a median of 39 months of treatment. This study also showed that a decline in HBcrAg was the only predictor of HBeAg loss after 78 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that baseline levels and changes in HBcrAg while on antiviral therapy may predict HBeAg loss or seroconversion after patients receive nucleos(t)ide analog or peginterferon therapy. [ 18 , 19 , 36 ] Wang et al [ 18 ] discovered that a combination of HBcrAg and HBsAg levels at month 6 (with AUROC 0.769) or month 12 (with AUROC 0.807) had the greatest predictive value for HBeAg seroconversion, in which 36.4% (43/118) of patients achieved HBeAg seroconversion after a median of 39 months of treatment. This study also showed that a decline in HBcrAg was the only predictor of HBeAg loss after 78 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests a possible role of serial monitoring of HBcrAg in clinical practice. In fact, in a study reporting serial HBcrAg levels among 50 patients undergoing HBeAg seroconversion on nucleos(t)ide analog therapy, the mean HBcrAg at the time of HBeAg seroconversion was 5.34 log U/mL 14 . Similarly, in a study in the United Kingdom, an HBcrAg level of < 5.5 log U/mL at 12 months of nucleos(t)ide analog treatment could best predict HBeAg seroconversion in 43 patients after a median of 39 months' treatment 15 …”
Section: Discussionmentioning
confidence: 99%
“…mean HBcrAg at the time of HBeAg seroconversion was 5.34 log U/mL. 14 Similarly, in a study in the United Kingdom, an HBcrAg level of < 5.5 log U/mL at 12 months of nucleos(t)ide analog treatment could best predict HBeAg seroconversion in 43 patients after a median of 39 months' treatment. 15 HBcrAg levels have been shown to be higher among patients with HBeAg-negative chronic hepatitis than those with HBeAg-negative chronic infection in previous studies.…”
mentioning
confidence: 94%
“…22 HBV DNA was undetected. 30 HBcrAg >5.7 log 10 U/mL was an independent predictor of recurrence during HBeAg seroconversion (adjusted Hazard Ratio 1.855, P = .021; 95% CI: 1.099-3.133) 31 and could be detected even if HBsAg lost. 32 In immunosuppressive patients with haematologic malignancies, both HBsAg and HBV DNA were negative, HBcrAg was positive and significantly associated with HBV reactivation (HRs 3.65, P = .011, 95% CI: 1.35-9.86).…”
Section: Empty Virusmentioning
confidence: 97%